2017
DOI: 10.1002/glia.23238
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine cross‐reacts with adrenoreceptors in cortical astrocytes to induce BDNF expression, CREB signaling and morphological transformation

Abstract: Expression of brain-derived neurotrophic factor (BDNF) is induced in cultured rat cortical astrocytes by catecholamines norepinephrine and dopamine as well as selective a1 and b adrenergic agonists. However, it has remained unknown which receptors mediate dopamine-induced BDNF upregulation in astrocytes. Here, we demonstrate that b adrenoreceptors are the main mediators of this effect in cultured cortical astrocytes, while a1 adrenoreceptors and D1 dopamine receptors contribute to a lesser extent. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 43 publications
(84 reference statements)
1
61
0
Order By: Relevance
“…It is shown that dopamine as well as norepinephrine induces BDNF expression in cultured astrocytes. 59 The effects of dopamine are brought about by its cross-reactivity with norepinephrine receptors. 59 Hence, astrocytic norepinephrine receptors may cell autonomously induce BDNF secretion in response to norepinephrine-enhancing antidepressant drugs.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that dopamine as well as norepinephrine induces BDNF expression in cultured astrocytes. 59 The effects of dopamine are brought about by its cross-reactivity with norepinephrine receptors. 59 Hence, astrocytic norepinephrine receptors may cell autonomously induce BDNF secretion in response to norepinephrine-enhancing antidepressant drugs.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“… 59 The effects of dopamine are brought about by its cross-reactivity with norepinephrine receptors. 59 Hence, astrocytic norepinephrine receptors may cell autonomously induce BDNF secretion in response to norepinephrine-enhancing antidepressant drugs. Such mechanisms need more thorough investigation as they may lie at the heart of mechanism of action of antidepressant drugs.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
See 1 more Smart Citation
“…NE can also enhance BDNF transcription and BDNF/TrkB kinetics ( Chen et al, 2007 ). Activation of the β1-adrenergic receptor stimulates BDNF transcription in astrocytes ( Koppel et al, 2018 ). When BDNF binds to TrkB, signal transduction is mediated by TrkB dimerizing and autophosphorylating ( Haniu et al, 1997 ).…”
Section: Neuroprotective Effectsmentioning
confidence: 99%
“…As we have well known, astrocytes can secrete several neurotrophic factors, such as brain-derived neurotrophic factor (BDNF) (Koppel et al, 2018), fibroblast growth factor (FGF) (Kajitani et al, 2015;Zhang et al, 2009), and vascular endothelial growth factor (VEGF) (Ijichi, Sakuma, & Tofilon, 1995). It has been reported that BDNF and FGF can modulate neurogenesis (Kang & Hebert, 2015), brain development (Marte, Messa, Benfenati, & Onofri, 2017;Shimada, Yoshida, & Yamagata, 2016).…”
mentioning
confidence: 99%